Mobile Controlled Smart Irrigation Systems, Fabrication, and Experimental Insights (International Journal of Communication Systems and Network Technologies, 2020)
The advent of smart technologies has revolutionized traditional agricultural practices, offering more efficient and precise approaches to irrigation management. This paper presents the design, fabrication, and experimental insights of a mobile-controlled smart irrigation system. The primary objective is to enhance water utilization in agriculture by integrating sensors, microcontrollers, and mobile communication. The system employs soil moisture sensors to monitor the realtime moisture content of the soil. A microcontroller processes the sensor data and bases it on predefined thresholds, triggering the irrigation system when necessary. The novelty of the system lies in its integration with a mobile application, allowing farmers to remotely control and monitor irrigation processes using a user-friendly interface. Experimental trials were conducted to evaluate the system’s performance under varying environmental conditions. Results indicate a significant improvement in water efficiency compared to traditional irrigation methods. The mobile-controlled interface provides farmers with flexibility, enabling them to respond promptly to changing conditions and optimize water usage.
Keywords: Smart Irrigtaion; Mobile Control; IOT; Sensor-based Irrigation; Microcontroller; Soil Moisture Sensors